2006
DOI: 10.1111/j.1747-0285.2006.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Generation of Long‐distance Structural Changes in Antibodies upon their Binding to Antigen

Abstract: An allosteric mechanism for the generation of long-distance structural alterations in Fab fragments of antibodies in immune complexes has been postulated and tested in theoretical and experimental analysis. The flexing and/or torsionderived forces exerted on the elbow region in Fab arms of bivalent antibodies upon binding to antigen were assumed to drive the disruption of hydrogen bonds which stabilize N-and C-terminal chain fragments in V-domains. This allows an extra movement in the elbow followed by a relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…to increase its polarity and solubility, reduce cell entry and facilitate excretion, which further lowers the toxicity of components carried by the supramolecular system [14][15][16]. Supramolecular CR interacts with proteins, although it is an atypical ligand, which binds outside the active group of the protein [17][18][19][20]. There are also reports of bacteria interacting with CR [21][22][23].…”
Section: Silver Complexes With Ty In the Supramolecular Cr Systemmentioning
confidence: 99%
“…to increase its polarity and solubility, reduce cell entry and facilitate excretion, which further lowers the toxicity of components carried by the supramolecular system [14][15][16]. Supramolecular CR interacts with proteins, although it is an atypical ligand, which binds outside the active group of the protein [17][18][19][20]. There are also reports of bacteria interacting with CR [21][22][23].…”
Section: Silver Complexes With Ty In the Supramolecular Cr Systemmentioning
confidence: 99%
“…A possible mechanism for the effect of a conformational change in the CH1-1 loop on Ag binding could be a change in the CH1-1 loop microenvironment, as a result of effector binding or a change in the hinge region, which may result in a change to the CH1-CL relative orientation. As discussed above and suggested previously (26,28,62), this may lead to changes in the VH-VL relative orientation through the elbow angle and, thus, to changes in the Ag binding site. Such a mechanism is also consistent with a recent analysis that found a large difference in affinity between a Fab and its corresponding Fv fragment (12).…”
Section: Discussionmentioning
confidence: 98%
“…Tudor et al (24) even suggested that the epitopes recognized by two anti-HIV-1 IgG1 and IgA2 Abs with identical variable domains are only partially overlapping. Furthermore, several studies suggested that long-distance structural changes may be transferred in the other direction as well, from the variable to the constant domain, potentially influencing effector activation (10,(25)(26)(27). For example, Oda et al (25) showed that the binding of staphylococcal protein A (SPA) or streptococcal protein G to the constant domain was inhibited by hapten binding in several mAbs.…”
mentioning
confidence: 99%
“…It should also be noted that the actual (observed) hydrophobicity density distribution may deviate from the idealized model, and that such local deviations are often tightly coupled to the protein's biological function, including potential deformations by which the protein fulfills its purpose. This specificity is readily evident in immunoglobulin domains discussed in [56][57][58].…”
Section: Proteins With Vniti Sequences Adopting β-Conformationsimmunomentioning
confidence: 90%